IMPLEMENTASI PERHITUNGAN PAJAK PENGHASILAN ATAS TRANSAKSI E-COMMERCE PADA DEARSI TOSERBA KABUPATEN TUBAN - Sinta Aprilia Putri Anggraini; Levi Martantina; Diah Anugrah Sharasanti (ITB AAS INDONESIA, 2024)
Dearsi Department Store is an E-Commerce business in the field of fashion which was founded by individuals with a founder named Ms. Arsi. Since its inception, Dearsi Toserba has never recorded transactions and made financial reports. That way the author tries to help make Dearsi Toserba Financial Reports with the Si Apik Application. The Si Apik application developed by BI in collaboration with IAI records transactions using a double entry (debit-credit) system so as to produce more accurate financial records. Besides that, Dearsi Department Store also never calculates the tax owed due to a lack of knowledge about taxation. Even though Dearsi Department Store has a fairly high turnover and the tax can be calculated using PP Number 55 of 2022. In PP Number 55 of 2022 it is explained that the final PPh rate of 0.5% for individual taxpayers is imposed for gross income above IDR 500,000,000 in one tax year. This means that the individual taxpayer's share of gross turnover of up to IDR 500,000,000 in one tax year is not subject to income tax. The amount of the share of gross turnover that is not subject to PPh is the total gross turnover of business which is calculated cumulatively since the first Tax Period in a Tax Year or part of a Tax Year. Thus, if the total gross income of an individual person does not exceed IDR 500,000,000 in one tax year, then no tax is payable on that income.